FAKTOR FAKTOR PENYEBAB DAN UPAYA PENANGGULANGAN TINDAK PIDANA PERSETUBUHAN YANG DILAKUKAN AYAH TERHADAP ANAK KANDUNG DI KOTA RUTENG KABUPATEN MANGGARAI - Jehalut, Yulius Jesaldi; kadja, Thelma; Fallo, Debi (Artemis Law Journal, 2023)
: Indonesia is a country that makes Pancasila a fundamental norm that upholds dignified human values, guarantees the creation of just and civilized human values. Pancasila is the basic instrument to avoid conflicts with the human rights of every citizen. The main problems in this thesis are: (1) What factors cause a biological father to have sexual intercourse with his own child? (2) What are the efforts to deal with this case? This research is empirical legal research carried out in Manggarai Regency. Data collection techniques use interview techniques and document study. The data used is primary data and secondary data. This research was conducted in the jurisdiction of the Manggarai District Prosecutor's Office. The results of data processing were analyzed descriptively qualitatively. The results of this research show: (1) The causal factors come from two sources, namely internal factors and external factors. (2) Countermeasures include pre-emptive efforts, preventive efforts and repressive efforts.